EXAMINING FACTORS PREDICTING EMPLOYEE WORK ENGAGEMENT AMONG CONTRACT STAFF OF COMMERCIAL BANKS IN OWERRI: THE ROLES OF PERCEIVED JOB INSECURITY AND EMPLOYEE TURNOVER INTENTION - Iwuala, Caleb Chukwuebuka; Ebeh, Richards E.; Obiagwu, Barbara A. (African Journal of Social and Behavioural Sciences, 2024)
The study investigated perceived job insecurity and employees’ turnover intention as predictors of employees’ work engagement among contract staff in commercial banks in Owerri, Nigeria. One hundred and seventy-three participants, comprising 70 males and 103 females, were selected from five commercial banks in Owerri, through the purposive sampling technique. Participants were between the ages of 22-53 years with a mean age of 35.01 and a standard deviation of 8.73. Three instruments; the Job Insecurity Scale by DeWitte (2000), Turnover Intention Scale by Mobley, et al (1978) and Utrecht’s Employee Engagement Scale by Schaufeli, et al (2002) were used for data collection. The design of the study was a cross-sectional survey design while data was analysed using hierarchical multiple regression. The results revealed that perceived job insecurity (β = -.778, p<.01, t = -16.21) and overall turnover intention (β = -.664, p>.01, t = -10.49) significantly predicted work engagement among contract staff of commercial banks in Owerri. Also, two of the three dimensions of turnover intentions namely job search behaviour (β = -.373, p<.01, t = -4.07) and psychological withdrawal (β = -.202, p<.01, t = -3.28), negatively predicted work engagement among contract staff of commercial banks in Owerri. However, job dissatisfaction (β = -.119, p>.05, t = -1.00) did not significantly predict work engagement among contract staff of commercial banks in Owerri. The researchers recommended, among others, that to mitigate perceptions of job insecurity among contract staff, commercial banks in Nigeria should consider hiring and converting contract staff to permanent staff positions. Ensuring equality in treatment and implementing clear job evaluation and performance management systems can further enhance job security and promote a sense of stability among all staff members.